コンピュータ ツウシン ネットワーク オ リヨウシタ ショウワキチ ノ コタイ チキュウ ブツリガク データノ デンソウ カンリ コウカイ ニツイテ - 金尾, 政紀; カナオ, マサキ; 神沼, 克伊; カミヌマ, カツタダ; 渋谷, 和雄; シブヤ, カズオ; 野木, 義史; ノギ, ヨシフミ; KANAO, Masaki; KAMINUMA, Katsutada; SHIBUYA, Kazuo; NOGI, Yoshifumi (1995)
P(論文) インマルサット衛星を利用した昭和基地(69.0°S, 39.6°E)の固体地球物理学データの伝送は, 第34次日本南極地域観測隊(JARE-34)から試験的に開始された。JARE-35は, 伝送用ワークステーションを地学棟に持ち込み, 国立極地研究所へのUUCP (Unix-to-Unix Copy)接続による伝送を開始した。JARE-36においては, データ伝送を継続すると共に, 観測状況などの情報交換に電子メールを利用している。昭和基地から伝送されたデータを含め, 広帯域地震計や超伝導重力計のデジタルデータについては, 国立極地研究所のワークステーションで管理しており, 国内外の研究者にインターネットを利用してのデータ公開を開始した。本稿では, 昭和基地からのデジタルデータ伝送について, その開始から1995年7月までの状況を報告すると共に, データの管理ならびに公開方法について紹介する。また, 最近の諸外国基地の地震波形データについてインターネットを利用した公開方法を紹介し, 今後の指針について検討する。 Data transmission of solid earth geophysics between Syowa Station (69.0°S, 39.6°E) and the National Institute of Polar Research (NIPR) was successfully made by the 34th Japanese Antarctic Research Expedition (JARE-34) in 1993 via the INMARSAT satellite telecommunication system. In 1994,data transmission from the Earth Science Laboratory (ESL) was started by JARE-35 using UUCP (Unix-to-Unix Copy) protocol for the file transfer. Electronical-mail services are also started by JARE-36 in May 1995; this is useful to exchange observational information easily. In addition to the hypocenters and phase arrival-times detected at Syowa Station, some digital waveform data from broadband seismometers and a superconducting gravity meter for recent several years are available from Internet services. They are stored in the directories under/pub/of UNIX workstation (IP address : 133.57.3.2), and accessible by use of 'anonymous ftp' command. We basically give priority of any data obtained at Syowa Station to the wintered-over JARE members with time limit of two years, and the data after the priority period go into a release mode. In this paper, the data transmission between Syowa Station and NIPR, the data archives in UNIX workstation, and data release using computer network are explained. The availability of digital waveform data of the other Antarctic stations is also introduced. departmental bulletin paper